Genetic Analysis of Signal Generation by the Rgt2 Glucose Sensor of Saccharomyces cerevisiae. Issue 8 (1st August 2018) - Scharff-Poulsen, Peter; Moriya, Hisao; Johnston, Mark
Abstract: The yeast S . cerevisiae senses glucose through Snf3 and Rgt2, transmembrane proteins that generate an intracellular signal in response to glucose that leads to inhibition of the Rgt1 transcriptional repressor and consequently to derepression of HXT genes encoding glucose transporters. Snf3 and Rgt2 are thought to be glucose receptors because they are similar to glucose transporters. In contrast to glucose transporters, they have unusually long C-terminal tails that bind to Mth1 and Std1, paralogous proteins that regulate function of the Rgt1 transcription factor. We show that the C-terminal tail of Rgt2 is not responsible for its inability to transport glucose. To gain insight into how the glucose sensors generate an intracellular signal, we identified RGT2 mutations that cause constitutive signal generation. Most of the mutations alter evolutionarily-conserved amino acids in the transmembrane spanning regions of Rgt2 that are predicted to be involved in maintaining an outward-facing conformation or to be in the substrate binding site. Our analysis of these mutations suggests they cause Rgt2 to adopt inward-facing or occluded conformations that generate the glucose signal. These results support the idea that Rgt2 and Snf3 are glucose receptors that signal in response to binding of extracellular glucose and inform the basis of their signaling.